Pengelolaan Timbunan Sampah untuk menjaga Citra Industri Pariwisata pada daya tarik Wisata di Bali - I Gusti Ketut Indra Pranata Darma; Ni Made Rai Kristina (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2021)
Bali is one of the islands with tourism potential that has grown rapidly. The fame of Bali Island tourism is well known to all corners of the world. Many of the people's daily activities become a tourist attraction for both domestic and foreign tourists. Every activity, especially those that give rise to this tourist attraction, produces waste both on a household and industrial scale. The waste produced is almost found in all sectors of activity, one of which is the tourism industry which is currently very much still moving. The increase in waste generation has prompted the government of Bali through the issuance of the Governor of Bali Regulation number 97 of 2018 concerning the limitation of single-use plastic waste, which shows the seriousness of the waste problem. Waste generation, especially in tourist attraction, has the potential to change the view of tourists on the image of Bali tourism. This research explores community movements both spontaneously and in an organized manner, such as the Trash Hero Indonesia community and other community activities that care about the high waste generation. It is hoped that alternative activities will be obtained to help reduce the generation of plastic waste that supports the implementation of Bali Governor Regulation number 97 of 2018. Activities from the community are expected to be able to maintain and provide a positive legacy for future generations.